Glycemic Control after Total Pancreatectomy for Intraductal Papillary Mucinous Neoplasm: An Exploratory Study. (26th August 2012) - Jamil, Laith H.; Chindris, Ana M.; Gill, Kanwar R. S.; Scimeca, Daniela; Stauffer, John A.; Heckman, Michael G.; Meek, Shon E.; Nguyen, Justin H.; Asbun, Horacio J.; Raimondo, Massimo; Woodward, Timothy A.; Wallace, Michael B.
Abstract : Background . Glycemic control following total pancreatectomy (TP) has been thought to be difficult to manage. Diffuse intraductal papillary mucinous neoplasm (IPMN) is a potentially curable precursor to pancreatic adenocarcinoma, best treated by TP. Objective . Compare glycemic control in patients undergoing TP for IPMN to patients with type 1 diabetes mellitus (DM). Design/Setting . Retrospective cohort. Outcome Measure . Hemoglobin A1C(HbA1C) at 6, 12, 18, and 24 months after TP. In the control group, baseline was defined as 6 months prior to the first HbA1c measure. Results . Mean HgbA1C at each point of interest was similar between TP and type I DM patients (6 months (7.5% versus 7.7%, P = 0.52 ), 12 months (7.3% versus 8.0%, P = 0.081 ), 18 months (7.7% and 7.6%, P = 0.64 ), and at 24 months (7.3% versus 7.8%, P = 0.10 )). Seven TP patients (50%) experienced a hypoglycemic event compared to 65 type 1 DM patients (65%, P = 0.38 ). Limitations . Small number of TP patients, retrospective design, lack of long-termfollowup. Conclusion . This suggests that glycemic control following TP for IPMNcan be well managed, similar to type 1 DM patients. Fear of DM following TP for IPMN should not preclude surgery when TP is indicated.